2000
DOI: 10.1002/(sici)1097-4547(20000315)59:6<775::aid-jnr10>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Early acute necrosis, delayed apoptosis and cytoskeletal breakdown in cultured cerebellar granule neurons exposed to methylmercury

Abstract: Cerebellar granule cells (CGCs) are a sensitive target for methylmercury (MeHg) neurotoxicity. In vitro exposure of primary cultures of rat CGCs to MeHg resulted in a time- and concentration-dependent cell death. Within 1 hr exposure, MeHg at 5-10 microM caused impairment of mitochondrial activity, de-energization of mitochondria and plasma membrane lysis, resulting in necrotic cell death. Lower MeHg concentrations (0.5-1 microM) did not compromise cell viability, mitochondrial membrane potential and function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(68 citation statements)
references
References 56 publications
3
64
0
1
Order By: Relevance
“…In human neural stem cells as well as in murine neural progenitor cells, MeHg was demonstrated to induce apoptosis at low cytotoxic concentrations and durations of exposure [ 1 0,50). In accordance to our data, Castaldi et al found an induction of apoptosis in mitotically inhibited cerebellar neurons at low MeHg hydroxide concentrations while at higher concentrations the compound induced necrosis [23). Additionally, incubation of thiomersal for 24 h in cultured human neurons induced apoptosis at low concentrations whereas high concentrations resulted in necrosis [19).…”
Section: !I1oosupporting
confidence: 92%
See 1 more Smart Citation
“…In human neural stem cells as well as in murine neural progenitor cells, MeHg was demonstrated to induce apoptosis at low cytotoxic concentrations and durations of exposure [ 1 0,50). In accordance to our data, Castaldi et al found an induction of apoptosis in mitotically inhibited cerebellar neurons at low MeHg hydroxide concentrations while at higher concentrations the compound induced necrosis [23). Additionally, incubation of thiomersal for 24 h in cultured human neurons induced apoptosis at low concentrations whereas high concentrations resulted in necrosis [19).…”
Section: !I1oosupporting
confidence: 92%
“…Nevertheless, numerous studies are limited to the use of immature, proliferating neurons [8,9,11,18,19] or neurons during differentiation [20][21][22] to investigate developmental neurotoxicity. Representing a differentiated neural cell culture model, Castoldi et al investigated effects of MeHg on primary cultures of mitotically inhibited rat granule neurons [23]. Furthermore, neurite outgrowth was affected in a differentiated PC12 cell clone [24].…”
Section: Introductionmentioning
confidence: 99%
“…We used 10 μM MeHg, because the application of this amount of MeHg induces a significant deceleration of the speed of granule cell migration (Fig. 2 C and F), although prolonged application affects the viability of granule cells (36). In the case of Ca 2+ signaling, caffeine (stimulator of internal Ca 2+ release through ryanodine receptors, 1 mM) or NMDA (agonist of the NMDAtype glutamate receptors, 30 μM) markedly reduced the effect of MeHg on Ca 2+ spike frequency of granule cells (Fig.…”
Section: Mehg Slows Granule Cell Migration Independent Of the Mode Ofsupporting
confidence: 91%
“…Neuronal degeneration upon MeHg exposure has been reported to occur through apoptosis (Kunimoto, 1994;Toimela and Tähti, 2004;Castoldi et al, 2000). Nagashima et al (1996Nagashima et al ( , 1997 established that the degeneration patterns of cerebellar granule cells in MeHg-intoxicated rats were quite similar to the typical finding of apoptosis, which is one of the mechanisms of neuronal destruction in degenerative brain damage.…”
Section: Resultsmentioning
confidence: 99%